2015
DOI: 10.1111/boj.12360
|View full text |Cite
|
Sign up to set email alerts
|

Is it really you,Orthotrichum acuminatum? Ascertaining a new case of intercontinental disjunction in mosses

Abstract: Intercontinental disjunct distributions are a main issue in current biogeography. Bryophytes usually have broad distribution ranges and therefore constitute an interesting subject of study in this context. During recent fieldwork in western North America and eastern Africa, we found new populations of a moss morphologically similar to Orthotrichum acuminatum. So far this species has been considered to be one of the most typical epiphytic mosses of the Mediterranean Basin. The new findings raise some puzzling q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 70 publications
(117 reference statements)
0
27
0
Order By: Relevance
“…Although intercontinentally disjunct bryophyte species often form monophyla (Heinrichs et al., ; Vigalondo et al., ), accessions from different continents are often resolved in sister clades (Heinrichs et al., ). This pattern of geographically structured phylogenetic relationships suggests gene flow and interbreeding between populations on different continents has ceased, and this may be confirmed by detailed study (Medina, Lara, Goffinet, Garilleti, & Mazimpaka, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although intercontinentally disjunct bryophyte species often form monophyla (Heinrichs et al., ; Vigalondo et al., ), accessions from different continents are often resolved in sister clades (Heinrichs et al., ). This pattern of geographically structured phylogenetic relationships suggests gene flow and interbreeding between populations on different continents has ceased, and this may be confirmed by detailed study (Medina, Lara, Goffinet, Garilleti, & Mazimpaka, ).…”
Section: Discussionmentioning
confidence: 99%
“…Range estimation is a challenging theme in morphologically little differentiated groups of organisms and suitable to improve understanding of species diversity and evolution. Many bryophyte genera belong to these critical groups and are in need of thorough reinvestigation including integrative molecular-morphological approaches; however, to date, only a limited number of studies is available (Dong et al, 2012;Forrest, Salazar-Allen, Gudiño, Korpelainen, & Long, 2011;Hedenäs et al, 2014;Heinrichs et al, 2015;Renner et al, 2013;Vanderpoorten, Patiño, Dirkse, Blockeel, & Hedenäs, 2015;Vigalondo et al, 2016). These studies identified numerous morphologically not or weakly differentiated bryophyte species of which many have rather narrow ranges.…”
Section: Introductionmentioning
confidence: 99%
“…For trnG , the primers used were trnGf_leu (Stech et al ., ) and trnGr (Pacak & Szweykowska‐Kulinska, ), and the PCR program included one melting step of 5 min at 94 °C, followed by 40 cycles of 30 s at 94 °C, 40 s at 52 °C and 1 min 30 s at 72 °C, and a final extension period of 8 min at 72 °C. For trnL ‐ trnF , the primers used were trnLc‐104 and trnFF‐425 (Vigalondo et al ., ). The PCR program included one melting step of 5 min at 94 °C, followed by 38 cycles of 30 s at 94 °C, 1 min at 47 °C, 30 s at 72 °C and 30 s at 94 °C, and a final extension period of 1 min at 72 °C.…”
Section: Methodsmentioning
confidence: 97%
“…Many extant mosses have intercontinental ranges; in a striking example, Orthotrichum acuminatum H. Philib., with documented occurrences in the western Nearctic, the western Palearctic, and Paleotropical eastern Africa, demonstrates that in mosses it is not impossible even for single species to have multiplecontinent disjunct ranges (Vigalondo et al 2016). Whereas the phylogenetic position of Steyermarkiella is unresolved, Alophosia is resolved as the basal-most member of Polytrichaceae in molecular phylogenetic analyses (Bell et al 2015).…”
Section: Early Cretaceous Bryophyte Diversity As Seen From Apple Baymentioning
confidence: 99%